“When I finished my film, I realized that people really needed me there”: the transformative power of Collaborative Filmmaking - Jessica G. Burke; Annika Agarwal; Mihaja Raonivololona; Tahiry Anjarasoa; Laura Leeson; Sara Baumann (Research Involvement and Engagement)
Abstract Collaborative Filmmaking (CF) is a relatively new, participatory, visual research method in which participants are trained in digital filmmaking to collect and analyze their own data in the form of creative short films and to disseminate their findings through film screenings and discussions. In this comment article, we present qualitative insights that delve into the perspectives of a group of CF participants as they reflect upon their experiences using CF and the impact that the method had on them as project participants. Participants were young adult educators who used CF to explore and evaluate the process of building community support for a comprehensive sexuality education (CSE) program in rural Madagascar. After the original project was completed, they participated in a focus group discussion with the researchers who created the method and answered questions about the process and impact of the method. The participants discussed the transformative power that CF has to elicit emotions and self-reflection among both filmmakers and audiences, and to generate visual evidence that can be used for education and advocacy about complex topics such as CSE.